Nematodes as Environmental Indicators - Wilson, Michael J (CABI, 2014)
Both of us are relatively new to the field of nematodes as biological indicators. We have backgrounds in crop protection and particularly the use of parasitic nematodes as biological control agents. In the late 1990s, we both obtained tenure track positions in institutions where there was a strong research emphasis on environmental diagnostics and bioremediation of contaminated land. Attendance at seminars given by students and visitors combined with conversations with colleagues made us both acutely aware of the potential nematodes offer as biological indicators. This potential exists from the sub-cellular to landscape scale. Perusing the literature made us realize that much high quality work had been done to exploit nematodes as biological indicators, but that information sources were diffuse with two problems (common to many fields of biology) being apparent: marine scientists rarely communicate with terrestrial scientists, and molecular biologists (particularly the Caenorhabditis eleganscommunity) have little contact with ecologists. If nematodes are to realize their true potential, these groups must communicate and collaborate. As a means of opening avenues of communication we organized the First International Symposium on Nematodes as Environmental Bioindicators, held in Edinburgh in June 2007